(untitled) (Global Business Management Review (GBMR), 2020)
The healthcare industry is becoming one of the most growing concerns among people in Malaysia. This industry is expected to provide efficient and effective services to the community. This study is aimed to examine the relationship between the dimension job burnout, which includes emotional exhaustion, personal accomplishment, and depersonalization with job satisfaction among healthcare providers in the healthcare industry at the northern part of Malaysia. A quantitative methodology was applied in this study where 200 questionnaires had been distributed. Only 171 questionnaires were collected and returned back. Out of that number, only 156 questionnaires were fit to be analysed. It was found that all of the burnout dimensions (emotional exhaustion, depersonalization, and personal accomplishment) have a significant relationship to job satisfaction. Multiple Regression analyses have found that 2 of the independent variables had a negative relationship with job satisfaction (emotional exhaustion and depersonalization). Personal accomplishment is the most significant and had a strong relationship with job satisfaction. It is recommended for future research to conduct qualitative research to find diversity in the result, emphasising on other professions, including a firefighter, police officer, custom immigration officer, or any other enforcement profession which seems to have an issue with job burnout. It is challenging to conduct this research due to the geographical location since the location for this study is in the northern part of Malaysia. It involves many hospitals, clinics as well as patient-oriented personnel. On the other hand, future research may include a bigger number of medical and healthcare personnel all over Malaysia to get a better generalisation. A wider scope of the population will provide better findings that cover all spectrum of the healthcare provider.